Deciphering Potential Role of Hippo Signaling Pathway in Breast Cancer: A Comprehensive Review - Bhavnagari, Hunayna; Raval, Apexa; Shah, Franky (Current Pharmaceutical Design, 2023)
Breast cancer is a heterogeneous disease and a leading malignancy around the world. It is a vital cause of untimely mortality among women. Drug resistance is the major challenge for effective cancer therapeutics. In contrast, cancer stem cells (CSCs) are one of the reasons for drug resistance, tumor progression, and metastasis. The small population of CSCs present in each tumor has the ability of self-renewal, differentiation, and tumorigenicity. CSCs are often identified and enriched using a variety of cell surface markers (CD44, CD24, CD133, ABCG2, CD49f, LGR5, SSEA-3, CD70) that exert their functions by different regulatory networks, i.e., Notch, Wnt/β-catenin, hedgehog (Hh), and Hippo signaling pathways. Particularly the Hippo signaling pathway is the emerging and very less explored cancer stem cell pathway. Here, in this review, the Hippo signaling molecules are elaborated with respect to their ability of stemness as epigenetic modulators and how these molecules can be targeted for better cancer treatment and to overcome drug resistance.
Keywords: Hippo signaling pathway